(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The aim of this study was to describe the results of endoscopic retrograde cholangiopancreatography (ERCP) treatment in children at Children’s Hospital 2. Methods: Retrospective case series. Results: From September 2022 to May 2024, 12 patients underwent ERCP. The median age was 12.9 years (range, 9 years 9 months to 15 years 2 months). Abdominal pain was the primary indication for hospitalization in 83.3% of cases. Imaging (abdominal ultrasound and MRI) showed bile duct dilation in all patients and prominent pancreatic duct dilation in 75%. Etiologies included intrahepatic and extrahepatic bile duct stones (10 patients) and Oddi sphincter stenosis (2 patients). Oddi sphincterotomy with stone extraction was the most frequent treatment. The medical procedure time was 87.5 minutes (range: 25-240 minutes). Treatment results: 100% of the stones were successfully removed. 100% of pain symptoms improved after the procedure. The medium length of stay was 14.8 days. The stone recurrence rate was 40%. Complications: 4 cases of acute pancreatitis, 2 cases of cholangitis, 1 case of biliary bleeding. No fatal complications were recorded. Conclusion: ERCP was performed successfully, effectively and safely in children at Children’s Hospital 2.